Specification for radio disturbance and immunity measuring apparatus and methods. Uncertainties, statistics and limit modelling. Statistics of complaints and a model for the calculation of limits for the protection of radio services Part 4-4, (13th May 2020) - British Standards Institution,
No abstract available